CONTRIBUTION TO PRODUCTION OF TURKISH NARROW-CLAWED CRAYFISH (PONTASTACUS LEPTODACTYLUS (ESCHSCHOLTZ, 1823), CAUGHT IN TURKEY: DISTRIBUTION IN KEBAN DAM LAKE - Dartay, Murside (Parlar Scientific Publications (P S P), 2021)
Keban Dam Lake is one of the most important freshwater reservoirs regarding fisheries production in the Eastern Anatolian region (Elazig, Turkey). This study was carried out from 1 July to 15 September in 2016 in Keban Dam Lake of Turkey. Crayfish fishing is usually done 10 weeks due to marketing problems crayfish in our region (the legal fishing duration being 5 months in July and December). The purpose of this study to determine of distribution and contribution to production of the crayfish captured by fyke-nets of local fishermen from different localities of the Keban Dam Lake. The CPUE (Catch per unit effort) values were 1.98, 1.08, 0.83 individuals/fyke-net/night for fishing season in Agin, Keban, Cemisgezek regions, respectively in 2016. The annual catch of crayfish was estimated as 13.15 tonnes. The length and weight compositions of crayfish captured in the fyke-nets have varied between 100 and 140 mm, and 52 and 90 g, respectively. The mean length and weight were found as 116 mm and 71.33 g for legal-sized individuals, The contribution of the Keban Dam Lake of this total production was 2.55 % in Turkey.
Keywords: Crayfish; Catch Per Unit Effort; Fyke nets; Keban Dam Lake; Turkey